Financial Performance Registered at IDX BUMN20 After The Covid-19 Pandemic in Indonesia: an Analysis of Abnormal Return, Trading Volume, and Bid-Ask Spread (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
The COVID-19 pandemic that rocked the globe has had numerous repercussions not only on human health but has had a considerable influence on Indonesia's economy, which has led several sectors to encounter various issues during the current pandemic, one of which was in the banking sector. IDX BUMN20 is a sector that the COVID-19 epidemic has also hit. The goal of this research was to evaluate disparities in financial performance during the COVID-19 pandemic in the banking sector listed on IDX BUMN 20 on the Indonesia Stock Exchange during the 2021–2022 timeframe as observed through anomalous returns, trading volume activity, and bid-ask spread. The research strategy employed is event study research employing quantitative approaches. The analytical approach employed is the paired sample test. The findings of the research reveal that there has been no change in the average abnormal return, trading volume activity, or the average bid-ask spread after the pandemic. Keywords: COVID-19, Abnormal return, bid-ask spread, trading volume activity, banking